Implementasi Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 5 Pada Penyelenggaraan Haji dan Umrah Kementerian Agama Kota Lhokseumawe - Nova Amalia (LPPM-UNIKI, 2023)
Hajj and Umrah Organizer, Office of the Ministry of Religion, Lhokseumawe City, as the institution responsible for organizing the Hajj and Umrah, is faced with complex challenges related to information and technology management. This research determines the process domain of Control Objectives using the COBIT 5 Framework and analysis of Capability Levels in Agencies. Based on the results of this research, it was found that the COBIT 5 domain processes used were EDM (Evaluate, Direct and Monitor), APO (Align, Plan and Organize), and MEA (Monitor Evaluate and Assess). The research results show that the agency's capability level is 2.29, which means it is still at level 2 (managed process), meaning the process has been carried out regularly, there is planning and supervision. Therefore, recommendations are needed for target levels to be achieved at level 3 by improving documentation of information technology management processes and developing requirements, classifications and priorities in providing services and handling incidents.